Aerococcus urinae and Aerococcus sanguinicola: Susceptibility Testing of 120 Isolates to Six Antimicrobial Agents Using Disk Diffusion (EUCAST), Etest, and Broth Microdilution Techniques - Carkaci, Derya (Open Microbiol J, 2017)
BACKGROUND: Aerococcus urinae and Aerococcus sanguinicola are relatively newcomers and emerging organisms in clinical and microbiological practice. Both species have worldwide been associated with urinary tract infections. More rarely cases of bacteremia/septicemia and infective endocarditis have been reported. Treatment options are therefore important. Just recently, European recommendations on susceptibility testing and interpretive criteria have been released. OBJECTIVE: In this investigation 120 A. urinae and A. sanguinicola isolates were tested for susceptibility to six antimicrobial agents: Penicillin, cefotaxime, meropenem, vancomycin, linezolid, and rifampicin. METHODS: Three susceptibility testing methods were used; disk diffusion according to The European Committee on Antimicrobial Susceptibility Testing (EUCAST) standardized disk diffusion methodology and MIC determination with Etest and broth microdilution (BMD). All testing was performed with EUCAST media for fastidious organisms. RESULTS: Data obtained in this study were part of the background data for establishing EUCAST breakpoints. MIC values obtained by Etest and BMD were well correlated with disk diffusion results. CONCLUSION: All isolates were found susceptible to all six antimicrobial agents: penicillin, cefotaxime, meropenem, vancomycin, linezolid, and rifampicin.